Critical analysis of surgical difficulties and postoperative morbidities of caesarean deliveries: a rural teaching hospital experiences in silk city, South India - Sheela, Wills G.; M., Chellatamizh; M., Mohanambal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Caesarean section is the delivery of a fetus through a surgical incision on the uterine wall after 28 weeks of gestation. Objectives of present study were to determine the caesarean section rate, to analyse surgical difficulties and post-operative morbidites in caesarean deliveries and to formulate modalities to reduce morbidity and to ensure safe motherhood. Methods: Retrospective analysis of caesarean deliveries in Shri Sathya Sai Medical College and Research Institute, Ammapettai from January 2015-2017. Total number of delivery in these two year were 494.Total vaginal delivery-210, Total caesarean delivery-284. Case records of women who had cesarean deliveries were analysed for intra operative complications and post-operative morbidity within the period of their hospital stay. Results: Total no of deliveries in 2 years were 494. Vaginal delivery was 210 (42.5%). Total caesarean section is 57.5% (n=284). Primary caesarean section rate 33.1% (n=94) and secondary cesarean section rate 66.9% (n=190). 60% of our subjects were un-booked emergency admissions. Majority were between 21-30 years. Youngest is 16yr old with imminent eclampsia, oldest 35yr with previous 3 LSCS with central placenta previa. Non-closure of peritoneum in previous caesarean has increased the risk of adhesions, plastered rectus muscle and bladder adhesion which caused difficulty in reaching lower segment in 62 women. In present study, vertical incision was put on uterus in 4 cases due to adhesions. Difficulty in entering uterine cavity, extension of uterine angle due to thick lower segment and excessive bleeding was seen in cases of repeat caesarean section. Scar dehiscence has increased due to single layer closure of uterus. Scar dehiscence was noted in 41 cases. Bladder injury in 3 cases, adherent placenta over the scar was seen in 5 cases. Conclusions: Caesarean section rate is increasing. Intraoperative complications and postoperative morbidity is comparatively less in primary caesarean section. More than one morbidity was seen in 60% women who had repeat section. With the growing rate of cesarean deliveries worldwide, women should be counselled that the repeat cesarean are bound with surgical difficulties and complications. If available, it’s imperative to take the senior obstetricians help for better surgical outcome. Anticipation of complications, early decision and active intervention reduces morbidity and prevent mortality as most of the women report for admissions late in labour.